Computing enabled me to... How Music and Programming Led Me to Build Digital Microworlds. - Sorensen, Andrew (Communications of the ACM, 2021)
A personal narrative is presented in which the author discusses how his interest in computer programming and music enabled him to build his career in programming music and sound.